Personality of Mirza Adeeb Through His Letters - Samina Aleem (بازیافت, 2018)
Letter writing is an old tradition in Urdu language. Mirza Adeeb's writing style is conversational which reveal many secret parts of his life. This tradition is still in practice. A very short number of his letters were available after his death which were given away to "GCUL". There are few letters not onely reflects many aspects of his personality,but also his deep relations with renowned scholars of his time.Bano Quddsiya and Tabish Delhvi wrote letters to Mirza in which they paid tribute to him on his services for the revival of Urdu literature. He was high decent fellow with whom people like to share their suffering and affairs. His letters are also important from historical point of view. He also wrote letters to his daughter "Naghma Adeeb" which highilghts his personal life as a loving and caring father. We also find literary information from his letters. No doubt his letters to his predecessors are very important from literary as well as historical point of view.